THE VALUE OF CHARACTER EDUCATION IN HAJJ PILGRIM (STUDY OF QS AL-BAQARAH/2:114) - Albahri, Albahri; Abubakar, Achmad; Ilyas, Hamka (Program Pascasarjana, UIN Alauddin Makassar, 2022)
This study aims to analyze the value of character education in the Hajj verses to produce an extract of character education value. It is expected as an offer of thought from the Al-Qur’an as an authentic source to shape personal, family and community character. This type of study was qualitative literature, the primary data obtained through written and digital literature. It used an interpretive descriptive data analysis method with a thematic approach to describe and analyse the Hajj verses about the value of character education. The results of this study indicated that the verse related to Hajj is in QS Al-Baqarah/2: 114. This verse conceived the value of character education, and the author divided it into four categories; first: the characters related to Allah, such as taqwa, istiqamah, gratitude, sincere, patient, not negligent heart, second: the characters related to humans, such as tolerance, favoring deliberation, collaborative, hardworking, honest, keeps promises, fair, compassionate, iffah, third: the character of the social environment sensitivity such as loving the environment and animals, science lover, social care, fourth: the character of the strength of belief: visionary, optimism, mission maturity and strength of belief.